Population-based study on prognostic factors for recurrence and progression in primary stage T1 bladder tumours. (June 2012) - Olsson, Hans; Hultman, Per; Rosell, Johan; Jahnson, Staffan
Abstract Objective. Stage T1 urothelial carcinoma of the bladder (UCB) exhibits heterogeneous clinical behaviour, and the treatment is controversial. The aim of this study was to evaluate prognostic factors for UCB in a defined, population-based cohort comprising patients with a first time diagnosis of primary stage T1 UCB. Material and methods. The study population initially consisted of 285 patients with primary stage T1 UCB reported to the regional Bladder Cancer Registry in the Southeast Healthcare Region of Sweden from 1992 to 2001. The histological specimens were re-evaluated concerning stage, substaging of T1, World Health Organization (WHO) grade, lymphovascular invasion (LVI), tumour volume and total resected volume. Hospital records provided data on tumour size and multiplicity, occurrence of possible relapse and/or progression, death from UCB and whether treatment was given. Results. After re-evaluation, the study population comprised 211 patients. The median follow-up time was 60 months. LVI was a prognostic factor for UCB progression and recurrence. Tumour size larger than 30 mm and multiplicity increased the risk of recurrence. T1 substaging, tumour volume and total resected volume were not associated with recurrence or tumour progression. Conclusions. LVI is significantly correlated with progression and recurrence in patients with primary stage T1 UCB. Therefore, the presence of LVI should be evaluated in every new case of T1 UCB.